Effect of Process Parameters on the critical attributes of the Liposomal formulations - Bayan Abu Ras; Youssef Haggag; Mohammad Isreb; Mohamed El Tanani (University of Huddersfield Press, 2022)
This study investigate the effect of process parameters on the size, distribution, zeta potential and loading efficiency for the co-delivery of liposomal formulation of Ran-RCC1 inhibitory peptide (RANIP) and doxorubicin (DOX) to breast cancer. The results show that drug concentration, pH and ultrasound intensity are all critical factors to control the attributes of the liposomes.